Arms and the Man - Shaw, Bernard, 1856-1950 (Salt Lake City, UT : Project Gutenberg, 2003)
"Arms and the Man" by George Bernard Shaw is a comedy first produced in 1894. Set during the Serbo-Bulgarian War, the play follows Raina, an idealistic young Bulgarian woman engaged to a battlefield hero, whose romantic notions are challenged when a pragmatic Swiss mercenary takes refuge in her bedroom. Shaw humorously exposes the futility of war and the hypocrisies of human nature as characters grapple with the gap between romantic ideals and reality, leading to unexpected revelations and shifting allegiances. (This is an automatically generated summary.)
Wikipedia page about this book: https://en.wikipedia.org/wiki/Arms_and_the_Man
Release date is 2003-01-01
Jim Tinsley with help from the distributed proofreaders
Keywords: War -- Drama; Love -- Drama; Man-woman relationships -- Drama; Serbo-Bulgarian War, 1885 -- Drama; Italians -- Bulgaria -- Drama; Soldiers -- Bulgaria -- Drama; Bulgaria -- Drama